2014
DOI: 10.1590/2176-9451.19.1.069-076.oar
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of NiTi and CuNiTi wires used in orthodontic treatment. Part 2: Microscopic surface appraisal and metallurgical characteristics

Abstract: ObjectiveThis research aimed at comparing the qualitative chemical compositions and the surface morphology of fracture regions of eight types of Nickel (Ni) Titanium (Ti) conventional wires, superelastic and heat-activated (GAC, TP, Ormco, Masel, Morelli and Unitek), to the wires with addition of copper (CuNiTi 27ºC and 35ºC, Ormco) after traction test. MethodsThe analyses were performed in a scanning electronic microscope (JEOL, model JSM-5800 LV) with EDS system of microanalysis (energy dispersive spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 12 publications
3
39
1
2
Order By: Relevance
“…On the other hand, in an attempt to explore the principal risk factors involved in the increased adherence activity of S. Those results determined that the surface morphology of NiTi samples had the lowest wire-surface roughness and the best chemical and mechanical properties, while those that presented the greatest and inadequate wire-surface roughness, deactivation loadings biologically less favorable in relation to the other heat-activated NiTi archwires, more degradation within the oral cavity, the highest corrosion risk and others, were also reported for CuNiTi wires [32][33][34][35]. Our results agree with those reported studies in which SEM and AFM images demonstrated that the CuNiTi wires presented more irregular surface topography with large amount of micropores and well-defined and irregular cavity surfaces, while NiTi and SS archwires had generally more smooth surfaces with slight scratches on their surfaces ( Figures 5 and 6).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, in an attempt to explore the principal risk factors involved in the increased adherence activity of S. Those results determined that the surface morphology of NiTi samples had the lowest wire-surface roughness and the best chemical and mechanical properties, while those that presented the greatest and inadequate wire-surface roughness, deactivation loadings biologically less favorable in relation to the other heat-activated NiTi archwires, more degradation within the oral cavity, the highest corrosion risk and others, were also reported for CuNiTi wires [32][33][34][35]. Our results agree with those reported studies in which SEM and AFM images demonstrated that the CuNiTi wires presented more irregular surface topography with large amount of micropores and well-defined and irregular cavity surfaces, while NiTi and SS archwires had generally more smooth surfaces with slight scratches on their surfaces ( Figures 5 and 6).…”
Section: Discussionmentioning
confidence: 95%
“…Our results agree with those reported studies in which SEM and AFM images demonstrated that the CuNiTi wires presented more irregular surface topography with large amount of micropores and well-defined and irregular cavity surfaces, while NiTi and SS archwires had generally more smooth surfaces with slight scratches on their surfaces ( Figures 5 and 6). This information suggests that the particular topographic and chemical conditions in each type of orthodontic wire could be considered as a relevant risk factor to promote significant irregular surfaces and more superficial area on the surface of orthodontic wires, principally in CuNiTi samples [32,33], permitting an increased bacterial adherence of S. mutans microorganism in regular conditions [6]. It is possible that the effect of AgNPs in the adherence activity of S. mutans bacteria on these orthodontic brackets and wires is due to various possible risk factors, such as particular microbiology characteristics of the microorganism, physical and chemical conditions of the used orthodontic appliances, and specific physicochemical properties of the AgNPs, in which several specific activities might synergistically be involved in the adherence activity of the S. mutans bacteria in these orthodontic tools.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the increase in surface roughness and surface free energy of archwires caused an increment in bacterial adhesion . Watanabe et al, Krishnan et al and Doshi et al reported that TMA archwires have more surface roughness than NiTi archwires.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Kusy et al and Yousif et al noticed that NiTi archwires have more surface roughness than TMA archwires. Gravina et al reported that SE NiTi archwires have a smoother surface property than CuNiTi archwires. Yu et al noticed that NiTi and SE NiTi archwires have similar surface roughness.…”
Section: Discussionmentioning
confidence: 99%
“…To monitoring the evolution of the corrosion potential of wires after fretting-corrosion tests, 16,17 a potentiostat VoltaLab 301 connected to an electrochemical cell as shown in Figure 2, 18,19 is performed. The working electrode was the tested sample, and the reference electrode was a saturated calomel electrode (SCE).…”
Section: Electrochemical Analysismentioning
confidence: 99%